Analysis of Metaphor in The Song “Helena” by My Chemical Romance - Bonifasius Nathanael Adi Nugraha; Ni Ketut Widhiarcani Matradewi; I Komang Sumaryana Putra (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The goal of this study is to identify the of figurative language and the meanings they express in the lyrics of My Chemical Romance's song Helena. Two theories are used in this study. Knickerbocker and Reninger's (1963) theory of figurative language serves as the first theory, and Leech's (1981) theory of meaning serves as the second. The information was derived from My Chemical Romance's song "Helena"'s lyrics. The data was gathered using the documentation method. The qualitative research approach was used to analyse the data that had been gathered. The informal method was used to convey the analysis findings from the analysis. From the analysis of the data overall the results show that four instances of metaphor are present within the lyrics of the song. The analysis of the lyrics found that the meaning of the song is about death and the lost of a loved one and how grief and sorrow can drive someone into insanity.